STUDI KARAKTERISTIK BATA MERAH LOKAL BALI SEBAGAI DINDING - Ni Nyoman Rita Rahayu; I. A. M Budiwati; M. Sukrawa (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2016)
Abstract : This study was conducted to determine the characteristics of brick red walls. Red brick taken from a local brick manufacturer Gianyar, Tabanan and Negara refer to SNI 15-0686-1989. By using mortar 1: 4, 1: 5, 1: 6, 1: 7 and 1: 8, according to the rules SK SNI M-111-1990-03. Testing red brick wall refers to the standards set in SNI 03-4164-1996. The data measured in this study is the compressive strength, modulus of elasticity and flexural strength. Modulus of elasticity of the wall pair by way of experiment calculated using the equation defined BSEN 1052-1-1999 Brick walls Gianyar, Tabanan of mortar 1: 4 consecutive compressive strength characteristics are 1.22, 1.32 and 1.42 N / mm ². Based on the results obtained in the testing of masonry walls with mortar 1: 4 with the value of the average compressive strength of 11.13 N / mm ² are classified as class mortar (i) according to standard BS 5628-1-1992 characteristic compressive strength for all wall below the chart value pairs are characteristic compressive strength of masonry that is equal to 2.5 N / mm ². Average modulus of elasticity of masonry walls Gianyar of mortar 1: 4, 1: 5, 1: 6, 1: 7 and 1: 8, according to the equation obtained 1052-1-1999 BSEN 240, 191, 171, 156 and 154 N / mm ², masonry walls Tabanan of mortar 1: 7 and 1: 8 obtained elastic modulus of 356 and 344 N / mm ², masonry walls Negara of mortar 1: 7 and 1: 8 obtained elastic modulus of 363 and 348 N / mm ². When compared three types of masonry is based on the elastic modulus and compressive strength, then the resulting brick wall of Negara has the greatest value for the various types of mortar, followed by a later brick wall brick wall Tabanan, Gianyar. Flexural strength values ??by using the equations listed in SNI 03-4165-1996, for gianyar masonry walls with mortar 1: 4, 1: 5, 1: 6, respectively are 0.005, 0.004 , 0.004 N/mm2, brick Tabanan 0.009, 0.007, 0.005 0.009 N/mm2 and brick Negara, 0.008, 0.006 N/mm2. Testing by means of BS EN 1052-2-1999 be reviewed only for 1:4 mortar masonry walls flexural strength values ??produced an average of 0.0045 MPa, this value is very close to the value obtained from way SNI 03-4165-1996 is equal to 0.005 MPa.